2011
DOI: 10.1007/s11262-011-0588-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic diversity of porcine Norovirus and Sapovirus in Korea

Abstract: It is well known that Norovirus (NoV) and Sapovirus (SaV) identified in humans and pigs have heterogeneous genome sequences. In this study, a total of three strains of NoV and 37 strains of SaV were detected in 567 porcine fecal samples by RT-PCR, corresponding detection rates of 0.5 and 6.5%, respectively. Phylogenetic analyses were conducted using amino acid sequences of the partial RNA-dependent RNA polymerase (RdRp) and complete capsid proteins of both viruses to determine their genogroups. Analysis with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
2
19
1
3
Order By: Relevance
“…were high compared to results obtained from other studies in which the occurrence rates detected were 0.5% in Korean pigs [24], 1.2%…”
Section: Discussioncontrasting
confidence: 65%
“…were high compared to results obtained from other studies in which the occurrence rates detected were 0.5% in Korean pigs [24], 1.2%…”
Section: Discussioncontrasting
confidence: 65%
“…and GXIV?, respectively. Our analysis placed previously unclassified porcine strains Po/ F2-4, Po/F8-9, Po/DO19, and Po/2014P2 into GVII (20,22), which formed at least 3 distinct genetic clusters in the capsid phylogenetic tree (Fig. 1), including the prototypical GVII SaVs (Po/ K7, Po/F2-4, and Po/DO19, respectively).…”
Section: Resultsmentioning
confidence: 74%
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations